THU0600 Patients' Perception and Satisfaction of Waiting Time at Medical Outpatients. (15th July 2016) - Magro, R.; Aquilina, J.
Abstract : Background: Patient satisfaction is an important determinant of health care quality. Decreasing waiting time is imperative in achieving patient satisfaction. Objectives: The aim of this study was to determine the mean waiting time at medical outpatients and to assess waiting time satisfaction. A further aim was to identify factors that affect the patients' perceived waiting time. Methods: Data was collected through questionnaire responses from 190 patients attending medical outpatients between 20th March and 9th April 2013. This included demographic data, waiting time and service satisfaction, expected and perceived waiting time, level of boredom and comfort while waiting. Moreover the actual waiting time was noted by the observer. The relationship between expected and perceived waiting time; and between actual and perceived waiting time were in turn analyzed using scatter plots and correlation coefficients. Approval to carry out this study was obtained from the University Research and Ethics Committee. Results: The participants had a mean age of 53 (range 19 to 86), of which 59% were females. On a 10-point Likert scale, the mean waiting time satisfaction was 7.1, while the mean service satisfaction was 9.3. The mean expected waiting time was 65 minutes and the mean perceived waiting time was 55 minutes. The mean actual waiting time was 51 minutes.This study revealed that as perceived waiting time increased, patient satisfaction tended to decrease consistently and significantly (p <0.001). On the other hand, regression analysis revealed that perceived waiting time has a positive and significant linear relationship with the actual waiting time ( p <0.001) and the boredom levels of patients ( p <0.001). Patients seated comfortably had a significantly lower perceived waiting time that those who were not ( p <0.001). Perceived waiting time was not influenced by whether the patient was accompanied ( p =0.313) or being seen for the first time ( p =0.712). The patients reported that the provision of free tea or coffee, magazines or television, could help reduce boredom and divert their attention, thus reducing perceived waiting time and in turn enhancing satisfaction. 11% (21 patients) suggested that the operation of free wireless internet in the waiting areas would also reduce the level of their boredom during their wait. Conclusions: Overall service satisfaction was extremely positive, while waiting time satisfaction was moderate. Although reducing the actual waiting time may be difficult, altering patients' perceived waiting time may be beneficial to increase their satisfaction. This could be done by increasing their comfort and decreasing their boredom while waiting. Disclosure of Interest: None declared